Audit committee and corporate governance among Sarawak Public Listed Companies - Ngu, Leong Hui (Universiti Malaysia Sarawak, (UNIMAS), 2012)
In Malaysia, Malaysian Securities Commission mandates all companies listed in Bursa Malaysia to form audit committee. Audit committee is responsible to oversee the financial reporting process and take note of the financial reporting risk. This study examines the relationship between finn size and audit committee composition such as audit committee size, proportion independent director in audit committee, financial expertise in audit committee, and frequency of meeting by audit committee toward corporate governance among Sarawak pubJic listed companies. The 28 companies incorporated in Sarawak listed on Main Market in Bursa Malaysia for year 2006 - 2011 is investigated. The study identifies the corporate governance based on accrual ratio, the lower the accrual ratio, the higher the corporate governance. The Pearson Correlation Test is used to examine the relationship between dependent and independent variables. The finding indicates that there are no significant relationships between audit committee composition and finn size with corporate governance. This study revealed that the establishment of audit committee in Sarawak listed companies in Malaysia has yet to achieve success in its monitoring role.